On the Financial Sustainability of Earnings-Related Pension Schemes with 'Pay-as-You-Go' Financing and the Role of Government-Indexed Bonds - Robalino, David A.; Bodor, Andras (2012)
In this paper we reconsider the idea of an earnings-related pension system with reserves invested in indexed government bonds as a mechanism to both ensure financial sustainability and improve security. The paper starts by reviewing the characterization of the sustainable rate of return of an earnings-related pension system with pay-as-you-go financing. We show that current proxies for the sustainable rate, including the Swedish 'gyroscope', are not stable and propose an alternative measure that depends on the growth of the buffer-stock and the pay-as-you-go asset. Using a simple one-sector macroeconomic model that embeds a notional account pension system we then show how GDP-indexed government bonds, if combined with the right measure for the sustainable rate of return on contributions, could be used to generate a sustainable and secure earnings-related pension system, without becoming a fiscal burden. The proposal is particularly attractive for countries considering reforms to earnings-related systems that have accumulated a large implicit pension debt. In this case, the government bonds allow the financing of this debt in a transparent way. The proposed mechanism can also facilitate the transition to a fully funded pension system when the government bonds are allowed to be traded.